Effects and mechanisms of trifolin on attenuating hypertension-induced vascular smooth muscle cell proliferation and collagen deposition in vivo and in vitro - Aling Shen; Meizhu Wu; Zhi Guo; Farman Ali; Jinkong Wu; Hong Chen; Ying Cheng; Dawei Lian; Jun Peng; Min Yu; Keji Chen (Scientific Reports)
Abstract Trifolin exhibits anti-tumor activities; however, its effect on hypertension remains unknown. This study was performed to investigate trifolin’s potential therapeutic effects and underlying mechanisms of action on angiotensin II (Ang II)-induced hypertension in mice and Ang II stimulated A7R5 cells. Mice were randomly allocated into six groups: control, Ang II, Ang II + Trifolin (0.1 mg/kg), Ang II + Trifolin (1 mg/kg), Ang II + Trifolin (10 mg/kg), and Ang II + Valsartan (10 mg/kg). The hypertensive mouse model was constructed by infusing Ang II via a micro-osmotic pump (500 ng/kg/min), and trifolin, valsartan, or double distilled water was administered intragastrically once daily for 4 weeks. Blood pressure, vascular function, pathological morphology, and collagen deposition in Ang II infused mice and cell viability of Ang II stimulated A7R5 cells were assessed. A networking pharmacology analysis was performed to identify potential targets, pathways, and processes. These were verified by determining proliferating cell nuclear antigen (PCNA) expression, cell migration, collagen protein expression and related pathway activation in vivo and in vitro using masson, immunohistochemistry, cell counting Kit-8 assays, phalloidin staining, wound healing assays, and western-blotting. Different concentrations of trifolin effectively mitigated the rise in systolic blood pressure, diastolic blood pressure, mean arterial pressure, pulse wave velocity, abdominal aorta wall thickness, and collagen deposition of Ang II infused mice. Notably, higher concentrations of trifolin exhibited greater attenuation which was similar to the effects of valsartan (a positive control). Networking pharmacology analysis identified 105 common targets and various gene ontology processes. The Kyoto Encyclopedia of Genes and Genomes pathways analysis identified multiple enriched signaling pathways, including responses to wounding, phosphatidylinositol 3-kinase complex, oxidoreductase, PI3K/AKT, and FoxO signaling pathways. Consistently, trifolin treatment significantly down-regulated the expression of PCNA and the ratio of p-PI3K/PI3K and p-AKT/AKT in the abdominal aorta tissues. In vitro study indicated that trifolin consistently reduced the cell viability, down-regulated the expression of PCNA, collagen I and collagen III, and reduced the cell migration, as well as reduced the ratio of p-PI3K/PI3K and p-AKT/AKT (similar with the effect of PI3K inhibitor: LY294002) in Ang II stimulated A7R5 cells. Trifolin treatment attenuated the elevation of blood pressure, the proliferation and collagen deposition of VSMCs, and modulated multiple signaling pathways, including PI3K/Akt pathway. These results suggest that trifolin could be a potential therapeutic approach for treating hypertension.